Eco-Innovation for Sustainability in Traditional Herbal (Jamu) Agroindustry: OGSM-Gap Analysis Based on Employee Perception - Irawan, Norbertus Citra; Widodo, Zandra Dwanita; Darmaningrum, Kurniawati; Haryadi, Rahmat Catur; Yuniastuti, Faustina; Rakasiwi, Alifah Addin (Agroindustrial Journal, 2023)
This research is motivated by the importance of eco-innovation in traditional herbal medicine agroindustry by using local ethnobotanical raw materials to support sustainability and answer increasingly stringent market demands. This research aims to identify gaps between objectives, goals, strategies, and performance measurements related to eco-innovation in the traditional herbal medicine agroindustry based on employee perceptions. The data analysis method used is the OGSM-Gaps model by collecting data through questionnaires distributed to traditional herbal medicine agroindustry employees at the research location, namely Solo Raya. The research population was employees of the traditional herbal medicine agroindustry. The research sample was taken using a simple random sampling method of 100 respondents. The research results highlight the need for improvement in several aspects of the organization. First, organizations need to focus on providing education and training for salespeople or store staff so that they can provide accurate information about traditional herbal medicine products. Second, increasing the promotion and branding of traditional herbal medicine products is needed to broaden public understanding. Furthermore, increasing the competitiveness of traditional herbal medicine products in the market is a priority, with an emphasis on market research and product innovation. Finally, operational efficiency needs to be improved through operational audits, adopting more efficient technology, and involving employees in these improvement efforts. These improvement efforts will support the organization in achieving sustainability goals and sustainable business growth.